Multicystic dysplastic kidney: a review of eleven years (2000 - 2010) - Rios,Helena (2012)
Introduction. Multicysticdysplastic kidney is the most common form of renal dysplasia. The natural history of multicystic dysplastic kidney is involution of the affected kidney, which justifies conservative management. The aim of this study was to evaluate the clinical course of a group of children with multicystic dysplastic kidney and compare these results with a previous study conducted 1989 -2000 in the same clinic. Patients and Methods. Retrospective analysis of the medical records of all children with multicystic dysplastic kidney referred to the paediatric nephrology unit of a tertiary paediatric hospital 2000-2010. Results. Fifty-two children (54% female) with multicystic dysplastic kidney were studied. The mean age at the time of the first visit was nineteen months with a mean follow-up time of sixty-five months. Prenatal ultrasound showed renal abnormalities in 96% of the children, 80% of which were suggestive of multicystic dysplastic kidney. All children underwent renal ultrasound and renal scintigraphy, 48 (92%) had a voiding cystourethrography and two (4%) intravenous urography. Ten (19%) children had contralateral kidney anomalies without obstruction of urinary tract, with the most frequent being pelvicalyceal dilatation (5) and vesicoureteral reflux (5). Nephrectomy was performed in five children (10%). Indications for nephrectomy were increased multicystic dysplastic kidney size in two children, ureterocele in two and bladder diverticulum in one. Of the 47 children (90%) with conservative treatment, 21 (45%) had total kidney involution (over a mean follow-up of three years). Ten (19%) children had complications, eight (15%) of them had urinary tract infection, and two proteinuria. Conclusions. As in the 1989-2000 study, prenatal ultrasound was the main form of multicystic dysplastic kidney diagnosis and contralateral kidney anomalies remain frequent (19% vs.=29%). There has been a significant reduction in the number of intravenous urographies (4% vs. 45%). Conservative treatment has been the first choice in the last few years, accompanied by a reduction in nephrectomies (10% vs. 37%). The lack of clinical problems and good evolution of children with multicystic dysplastic kidney, justifies conservative management. As these children have only one functioning kidney, an adequate monitoring with renal ultrasound and assessment of blood pressure and renal function is essential.